Effect of NaOH Concentration on Surface Width and Pore Volume of Silica Gel From Beef Shrain as Adsorbent - Nurmutaaqimah; Siti Jamilatun; Aster Rahayu (Sains Natural: Journal of Biology and Chemistry, 2025)
Rice husk is a natural source of silica that has the potential to be utilized in various applications, especially in industrial wastewater treatment. This study aims to determine the effect of NaOH concentration on the surface area and pore volume of silica gel from rice husk as an adsorbent. The method used is sol-gel with variations in NaOH concentration, namely 1, 2, and 3 M. The process of making silica gel consists of four steps. The silica gel manufacturing process consists of four steps: (1) combustion of rice husk using a furnace, (2) preparation of sodium silicate solution, (3) formation of silica gel through the addition of HCl, and (4) sample testing. Based on XRF analysis, rice husk ash is rich in silica (SiO₂) with a concentration of up to 32.189%, while water content testing shows that the 2 M NaOH concentration provides the largest decrease in water content (96%), higher than the concentrations of 1 M and 3 M, which reach 95%, in line with the results of BET analysis showing optimum conditions at a concentration of 2 M producing the highest surface area (138.720 m²/g) and the largest pore volume (0.673 cm³/g). The 1 M NaOH concentration produced a smaller surface area of 73.869 m²/g with a pore volume of 0.501 cm³/g. Meanwhile, the 3 M NaOH concentration decreased the surface area to 111.626 m²/g with a pore volume of (0.640 cm³/g). Overall, the 2 M NaOH concentration proved to be the most effective in increasing surface area and pore volume. Thus, the resulting silica gel is very suitable for adsorption applications, especially in the treatment of industrial wastewater.